2015
DOI: 10.1007/s00432-015-2095-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating U2 small nuclear RNA fragments as a diagnostic and prognostic biomarker in lung cancer patients

Abstract: Serum RNU2-1f may serve as a biomarker for lung cancer detection, prognosis prediction and treatment monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Multiple prior studies have identified tantalizing connections between snRNAs and cancer. For example, overexpression of U1 snRNA may promote pro-cancer gene expression (Cheng et al 2017), and U2 snRNA fragments are potential blood-based biomarkers for multiple cancers (Baraniskin et al 2016;Kuhlmann et al 2014;Köhler et al 2016;Kuhlmann et al 2015). Intriguingly, we observed a clear association between snRNA levels and the intrinsic breast cancer subtypes (Sorlie et al 2001).…”
Section: Discussionmentioning
confidence: 64%
“…Multiple prior studies have identified tantalizing connections between snRNAs and cancer. For example, overexpression of U1 snRNA may promote pro-cancer gene expression (Cheng et al 2017), and U2 snRNA fragments are potential blood-based biomarkers for multiple cancers (Baraniskin et al 2016;Kuhlmann et al 2014;Köhler et al 2016;Kuhlmann et al 2015). Intriguingly, we observed a clear association between snRNA levels and the intrinsic breast cancer subtypes (Sorlie et al 2001).…”
Section: Discussionmentioning
confidence: 64%
“…RNU11 plays a role in splicing the U12-dependent class of eukaryotic nuclear introns and was found to be downregulated in TNBC samples. Although previous studies have shown the RNU family of snRNAs are expressed in pancreatic, colorectal and lung cancers, no concrete evidence is available to define the function of RNU2 snRNAs 72.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that transcriptional regulation of snRNA genes is involved in the carcinogenesis of several types of leukemia, lung cancer and germ cell tumors [19][20][21]. Our results raise the possibility that p53 inhibits transcription of snRNA genes through inhibiting the recruitment of LEC to MED26 and functions as an oncosuppressor.…”
Section: Discussionmentioning
confidence: 52%
“…It has been reported that p53 represses the transcription of snRNA genes [18]. In addition, accumulating evidence indicates that snRNA plays a role in the carcinogenesis in lung cancer, germ cell tumors and several types of leukemia [19][20][21] and in the progression of human diseases including Alzheimer's disease [22][23][24].…”
Section: Transcription Elongation Factors Including Eleven Lysine-ricmentioning
confidence: 99%